Characterization of Listeria monocytogenes isolated from poultry products and from the poultry-processing environment by random amplification of polymorphic DNA and multilocus enzyme electrophoresis. - Lawrence, L M (1995)
A total of 289 Listeria monocytogenes strains isolated from a poultry-processing environment and poultry products over a 6-month period were characterized by random amplification of polymorphic DNA, (RAPD) to pinpoint sources of contamination within the plant and gain some measure of the persistence of individual genotypes within this environment. Eighteen RAPD profiles (A through R) were identified within this group, with 64% (184 of 289) of all strains displaying a single RAPD profile, RAPD type A. This genotype was more prevalent in the raw-poultry-processing environment, where, although its origin within this environment appeared to be the incoming birds, it was also widespread on food contact surfaces, floors, and drains. This was the only genotype which persisted throughout the entire 6-month period, and it and RAPD type B were the only two genotypes found in both the raw- and cooked-poultry-processing environments. L. monocytogenes strains isolated from cooked poultry products and the cooked-poultry-processing environment up to 1 year later (17 strains) contained only RAPD types A and B, highlighting the potential which exists for persistent strains to cross-contaminate foods processed in that environment. The other genotypes (C through R) occurred more sporadically, suggesting varied sources of contamination. These were confined to either the raw- or the cooked-poultry-processing environment and were relatively short-lived. Further characterization of a selection of RAPD type A strains, together with strains of RAPD types B through R, was carried out by multilocus enzyme electrophoresis. Strains of RAPD type A contained two electrophoretic types, one of which was serotype 1/2a and the other was 1/2c.(ABSTRACT TRUNCATED AT 250 WORDS)